The status of s in Dominican Spanish - Bullock, Barbara E.; Toribio, Almeida Jacqueline; Amengual, Mark (Lingua, 2014)
•Gender and literacy are significant factors of s retention.•Intrusive-s occurs with low frequency among all speakers.•There is no correlation between rates of lexical-s use and intrusive-s use.•Lexical and intrusive-s are attracted to following voiceless stops. Theoretical linguistic treatments of the intrusive-s of popular Dominican Spanish (yo[s] tuve<yo tuve ‘I had’) assume the hypothesis that illiterate speakers have reanalyzed their phonologies so that lexical items no longer contain any trace of coda-s. As a consequence, illiterate speakers are said to restore an s into random syllable codas in an attempt to hypercorrect to a more elevated style. Using natural data gathered from sociolinguistic interviews with Dominicans of diverse literacy levels, we demonstrate that the phonological characterization of intrusive-s in the theoretical literature is incorrect and the hypothesis that illiterate speakers lack etymological /s/ is also shown to be flawed. Instead, the results of a quantitative analysis demonstrate that, despite high rates of s-deletion, overtly manifested s usually corresponds to etymological-s. Intrusive-s arises relatively rarely in our corpus and it appears from this data that lexical and intrusive-s might have distinct linguistic distributions and they may differ in what they mark socially.